Indian Philosophy (England : Taylor & Francis, 2013., 2017)
Frontmatter / S. Radhakrishnan -- Chapter I / unknown -- Part I The Vedic Period / unknown -- Part II The Epic Period / unknown -- Appendix / unknown -- Notes / unknown -- Index / unknown -- The Vedanta / unknown -- Indian Philosophy / unknown.